The hard challenge of aid co-ordination - François Bourguignon; Jean-Philippe Platteau (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Aid co-ordination is a constant theme of discussion among national and international aid agencies in their search for more effectiveness and efficiency in delivering development assistance. This paper seeks to clarify some of the arguments currently made in support of aid co-ordination, and to precise unavoidable trade-offs born of the existence of political costs. It is anchored in the available literature on aid delivery while focusing on the implementation problems of aid co-ordination among donor countries. In particular, it deals with: (a) the issue of consistently and collectively handling possible governance failures in recipient countries; and (b) the impact of heterogeneity of donor countries on the effectiveness of aid co-ordination.
Keywords: C1; O1; O2; O4; 330; development aid; co-ordination; aid efficiency